Drug-related Problems in Prescribing for Outpatients with Type 2 Diabetes at a District General Hospital in Hanoi - Thao, Nguyen Thi; Ha, Vu Thi; Hoa, Le Thi Thuy; Hoa, Nguyen Thi; Thi Thuy Van, Pham (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 41 No 3, 2025)
Objectives: This study aimed to identify drug-related problems (DRPs) in prescriptions for outpatients with type 2 diabetes mellitus (DM) at a district general hospital in Hanoi. Methods: The study included type 2 DM outpatients who underwent HbA1c testing between June 1 and June 30, 2023. A cross-sectional, whole-sample study design was utilized, with disease and medication data collected from patient medical records. DRPs were identified using a level 2B medication review based on the Pharmaceutical Care Network Europe (PCNE) classification. Initial DRP identification was conducted by pharmacists, followed by discussions with prescribing physicians for consensus. Results: A total of 289 patients were included in the analysis, resulting in the identification of 497 DRPs, averaging 1.7 DRPs per prescription. The most common DRPs involved lipid-lowering medications (55.6%) and hypoglycemic medications (37.2%). The majority of DRPs (89.1%) were attributed to insufficient treatment effectiveness (PCNE code P1), predominantly due to an inappropriate drug according to guidelines (PCNE code C1.1, accounting for 85.3%). Conclusions: DRPs in outpatient prescribing for type 2 DM primarily involve hypoglycemic and lipid-lowering medications. Enhanced clinical pharmacy services are essential to optimize prescribing practices in this patient population. Keywords: Drug–related problem, type 2 diabetes, outpatient.